Parametric study of gamma-type free piston stirling engine using nonlinear thermodynamic-dynamic coupled model. (15th November 2020) - Ye, Wenlian; Zhang, Ting; Wang, Xiaojun; Liu, Yingwen; Chen, Pengfan
Abstract: A reliable thermodynamic-dynamic coupled model for a gamma-type FPSE possessing nonlinear load damping coefficient has been proposed in this study. Simultaneously, the experimental results are compared with the model and a satisfactory agreement is obtained. The output power is predicted with less than 5% error under different hot-end temperatures. Then the amplitude of displacer and piston with time at different pistons' positions are obtained, and the effects of load damping and nonlinear coefficients on the amplitude values of two pistons and output power are presented. Finally, a simulation study is carried out to investigate the sensitivity of thermodynamic-dynamic parameters to the amplitude of two pistons, operating frequency and output power, and the fitting formulas for evaluating the performance of FPSE are presented. It is found that the initial positions of two pistons have little effect on pistons' amplitude in the FPSE nonlinear system. High charge pressure, hot-end temperature, and spring stiffness of the displacer can increase the output power and amplitude of the pistons while other parameters have a negative effect on them. The fitting equations have high accuracy. This work provides a reliable model and theoretical guidance for improving the FPSE's performance. Highlights: Nonlinear load model of a γ-type FPSE is validated with the experimental results. The amplitude variations with time at different pistons' positions are obtained. Performance of FPSE declines during the increase of nonlinear load damping. Influences of operating and dynamic parameters on the performance are analyzed. The fitting formulas for evaluating FPSE's performance are presented.